PENGATURAN DANA ALOKASI KHUSUS SEBAGAI DANA PERIMBANGAN ANTARAPEMERINTAH PUSAT DAN PEMERINTAH DAERAH - SUWIRYANATA, I NYOMAN; PARSA, I WAYAN; SUHARTA, I NENGAH (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 06, September 2013)
This paper to discuss about the Special Allocation Fund which used by the specificneeds of the district to finance in the respective regions, the Special Allocation Fundallocation is highly dependent on the availability of state funds sourced from TheCentral Government. The Problem is the criteria that must be met by an area to get aspecial allocation fund and What is the use of the Special Allocation Fund as the fundbalance to an area. In this paper author uses normative legal research and normativejuridical approach. The conclusion is, Criteria regions receiving the Special AllocationFund specified in namely Law Number 33 of 2004 on Financial Balance betweenCentral and Local Government, in this case the Special Allocation Fund It should beused or utilized to close the gap between local public services by giving priority toeducation, health, infrastructure, marine and fisheries, agriculture, infrastructure localgovernment and the environment.
Keywords: Special Allocation Fund, Central Government, Local Government